Antifibrinolytics in a rural trauma state: assessing the opportunities. Issue 1 (5th October 2017) - Bardes, James M; Palmer, Amanda; Con, Jorge; Wilson, Alison; Schaefer, Gregory
Abstract : Background: Tranexamic acid (TXA) has demonstrated improved mortality among trauma patients. However, recent evidence from urban US trauma centers has failed to show a benefit among the civilian population. TXA in rural states has not been evaluated. This study aimed to evaluate the current use of TXA in the rural trauma population. Methods: A retrospective observational review at a level 1 trauma center based in a rural environment. Records were reviewed for TXA indications. TXA indication was defined as: systolic blood pressure <90 mm Hg, blood transfusion, or with a clinical concern for ongoing bleeding. Patients were ineligible if the time since injury was >3 hours. Results: 400 patients were evaluated. 54% of patients met indications for TXA. 14% of these received TXA. 30.4% with an indication for TXA were ineligible due to arrival beyond 3 hours from time of injury. 135 patients arrived as transfers, 265 from the scene. There was no difference in TXA indications between scene and transfers (73 vs 144, p=1). Transfers were more likely to arrive beyond the 3-hour window (59 vs 7, p=0.001). Mortality for patients treated with TXA was 12.5%. This was not significantly different from patients not treated with TXA (19%). Discussion: In a rural system, long transfers exclude most patients from treatment with TXA. A multicenter rural trauma center study will be needed to better define the optimal use of TXA in rural populations. Level of evidence: Level IV data: therapeutic/care management.